2009
DOI: 10.1016/j.neuroimage.2008.12.033
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of automated segmentation and manual tracing for quantifying hippocampal and amygdala volumes

Abstract: Large databases of high-resolution structural MR images are being assembled to quantitatively examine the relationships between brain anatomy, disease progression, treatment regimens, and genetic influences upon brain structure. Quantifying brain structures in such large databases cannot be practically accomplished by expert neuroanatomists using hand-tracing. Rather, this research will depend upon automated methods that reliably and accurately segment and quantify dozens of brain regions. At present, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
478
6
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 508 publications
(529 citation statements)
references
References 23 publications
42
478
6
3
Order By: Relevance
“…For HC segmentation, recently published results (Barnes et al, 2008;Chupin et al, 2007;Morey et al, 2009;Morra et al, 2008;Pohl et al, 2007;van der Lijn et al, 2008) indicated high kappa index values greater than 0.80. The latest published methods based on the nonlinear warping of the best templates and involving a label fusion step (Collins and Pruessner, 2010;Gousias et al, 2008;Lotjonen et al, 2010) obtained kappa index values equal to or greater than 0.88.…”
Section: Discussionmentioning
confidence: 95%
“…For HC segmentation, recently published results (Barnes et al, 2008;Chupin et al, 2007;Morey et al, 2009;Morra et al, 2008;Pohl et al, 2007;van der Lijn et al, 2008) indicated high kappa index values greater than 0.80. The latest published methods based on the nonlinear warping of the best templates and involving a label fusion step (Collins and Pruessner, 2010;Gousias et al, 2008;Lotjonen et al, 2010) obtained kappa index values equal to or greater than 0.88.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, given the inherent limitations of any fully automated segmentation software, cortical and subcortical labelling may be influenced by several factors, such as section thickness, MRI noise level, field strength, MRI signal intensities in elderly subjects and anatomic boundary criteria. However, recent methodological studies (Morey et al, 2009;Jovicich et al, 2009) have demonstrated that Freesurfer can be considered an acceptable substitute for manual tracing of automatically quantified amygdala volume, although a large cohort of subjects is warranted. Second, the lack of a significant association between amygdala volume and MAO A VNTR polymorphism could be influenced by further social/psychological variables not taken into consideration in this work, such as impulsivity (Soloff et al, 2008), social disadvantage experiences such as trauma or abuse history (Caspi et al 2002, Kim-Cohen et al 2006 or cigarette smoking behaviour (Caporaso et al, 2009) that could ultimately interact with MAO A functioning.…”
Section: Discussionmentioning
confidence: 99%
“…This latter term represents a large number of constraints on the space of allowable segmentations and prohibits label configurations that never occur in the training set (e.g., the hippocampus is never anterior to the amygdala). This approach provides advantages similar to manual region-of-interest (ROI) drawing (Morey et al, 2009;Jovicich et al, 2009), without the potential for rater bias, offering an anatomically accurate rendering of regional volumes (Fischl et al, 2002). The entire cortex in each individual subject was visually inspected prior to analysis and, if needed, manually edited.…”
Section: Mri Sequence and Analysismentioning
confidence: 99%
“…The hippocampal volumes of all participants at each occasion were measured using the fully-automated FreeSurfer hippocampus segmentation, a method to obtain hippocampus volumes automatically, which has been shown to compare well with the gold standard of manual tracing (Morey et al, 2009). The raw images were preprocessed using the FreeSurfer longitudinal stream and a P b 0.05 threshold was applied to the paired t-test of hippocampal volume segmentations between LFP and EFP.…”
Section: Mri Data Acquisitionmentioning
confidence: 99%